Development of motivational strategies for face-to-face teaching of experimental physics in basic physics laboratories: a review - Grande Ccalla, Juan Carlos (2022)
A documentary review was carried out on the production and publication of research papers related to the study of the variable Elaboration of motivational strategies for teaching physics. The purpose of the bibliometric analysis proposed in this document, is to know the main characteristics of the volume of publications registered in Scopus database during the period 2015-2020 in Latin American countries, achieving the identification of 80 publications. The information provided by said platform, was organized by means of graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics were described, the position of different authors regarding the proposed topic was referenced by means of a qualitative analysis. Among the main findings of this research, it is found that Brazil, with 31 publications, is the Latin American country with the highest production. The area of knowledge that made the greatest contribution to the construction of bibliographic material referring to the study of the development of motivational strategies for the teaching of physics was social sciences with 47 published documents, and the type of publication that was most used during the periodmentioned above was the journal article, which represents 53% of the total scientific production.